(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve student learning outcomes in Natural Sciences (IPA) regarding the water cycle process. The study uses a Classroom Action Research (CAR) design conducted in two cycles, each through the stages of planning, implementation of actions, observation, and reflection. The research subjects were 14 fifth-grade students at SDN Weetebula II. Data were collected through observation of teacher and student activities, learning outcome tests at the end of each cycle, and supporting documentation during the learning process. The observation data were analysed descriptively to see improvements in the quality of the learning process, while the test data were analysed by comparing the class average scores and learning completeness between cycles. The results showed an increase in teacher activity from 73.95 in cycle I to 94.79 in cycle II, as well as an increase in student activity from 76.66 to 93.33. The use of audio-visual learning media also had a positive impact on student learning outcomes. The class average score increased from 65.46 with 64% mastery in cycle I to 80.07 with 92% mastery in cycle II. These findings prove that the use of audio-visual media is effective in improving students’ understanding of the water cycle and encouraging their active involvement in the learning process